Work Stress Among Bank Employees: A Case Study of Bank Rakyat (Malaysian Management Journal, 2013)
The extent of stress faced by skilled employees in organizations is often substantial. In several professions, stress is intrinsic to the duty itself, where competing demands, challenges and pressures escort the duty and therefore cannot be avoided. On the organizational level, stress exists in every company. The purpose of this study was to investigate the factors that contribute of to work stress among Bank Rakyat’s employees. This study also aimed to determine if there were any statistically significant differences in the respondents’ level of work stress by demographic factors (gender, status, education qualification, job position and length of service). The survey was carried out at 12 branches of Bank Rakyat in the northern region of the Malaysian Peninsula. A total 154 bank employees participated in this study. Data was collected through a 40-item questionnaire on a five-point Likert Scale. The findings of this study showed that only organizational factors had a significant influence on work stress level. The study also revealed that the overall level of work stress among the respondents was moderate. While on the difference between the level of work stress by demographic factors, this study found that there was no statistically significant difference between these factors.